Drivers of Holocene peatland carbon accumulation across a climate gradient in northeastern North America. (1st August 2015) - Charman, Dan J.; Amesbury, Matthew J.; Hinchliffe, William; Hughes, Paul D.M.; Mallon, Gunnar; Blake, William H.; Daley, Tim J.; Gallego-Sala, Angela V.; Mauquoy, Dmitri
Abstract: Peatlands are an important component of the Holocene global carbon (C) cycle and the rate of C sequestration and storage is driven by the balance between net primary productivity and decay. A number of studies now suggest that climate is a key driver of peatland C accumulation at large spatial scales and over long timescales, with warmer conditions associated with higher rates of C accumulation. However, other factors are also likely to play a significant role in determining local carbon accumulation rates and these may modify past, present and future peatland carbon sequestration. Here, we test the importance of climate as a driver of C accumulation, compared with hydrological change, fire, nitrogen content and vegetation type, from records of C accumulation at three sites in northeastern North America, across the N–S climate gradient of raised bog distribution. Radiocarbon age models, bulk density values and %C measurements from each site are used to construct C accumulation histories commencing between 11, 200 and 8000 cal. years BP. The relationship between C accumulation and environmental variables (past water table depth, fire, peat forming vegetation and nitrogen content) is assessed with linear and multivariate regression analyses. Differences in long-term rates of carbon accumulation between sites support the contention that a warmer climate with longer growing seasons results in faster rates of long-term carbon accumulation. However, mid-late Holocene accumulation rates show divergent trends, decreasing in the north but rising in the south. We hypothesise that sites close to the moisture threshold for raised bog distribution increased their growth rate in response to a cooler climate with lower evapotranspiration in the late Holocene, but net primary productivity declined over the same period in northern areas causing a decrease in C accumulation. There was no clear relationship between C accumulation and hydrological change, vegetation, nitrogen content or fire, but early successional stages of peatland growth had faster rates of C accumulation even though temperatures were probably lower at the time. We conclude that climate is the most important driver of peatland accumulation rates over millennial timescales, but that successional vegetation change is a significant additional influence. Whilst the majority of northern peatlands are likely to increase C accumulation rates under future warmer climates, those at the southern limit of distribution may show reduced rates. However, early succession peatlands that develop under future warming at the northern limits of peatland distribution are likely to have high rates of C accumulation and will compensate for some of the losses elsewhere. Highlights: Total peatland C accumulation is related to growing season conditions across a climate gradient. Peatlands at the southern limit of distribution show divergent trends to those in the north. Early succession peatlands have higher rates of peat accumulation. Projections of C sink changes need to account for spatially differentiated responses in peatlands.